Pivoting : a coach's guide to igniting substantial change - Clancy, Ann L.; Binkert, Jacqueline (Palgrave Macmillan, 2017)
Change is a necessary, though sometimes challenging part of staying relevant, being engaged and seeking ways to flourish in one's life. Coaching helps individuals develop coherent strategies for their life and work and to tap into their strengths and inspiration. Often our clients find themselves having to shift or transform their limiting belief systems or habits of mind and behavior to move them toward greater self-direction. How does such meaningful change occur? What role can coaches play to effectively lead our clients to new insights? To answer these questions, the authors set off on a scholar/practitioner journey of research, study, and first-hand experience to better comprehend the mystery and wonder of how clients actually make meaningful transitions. Their path of inquiry describes a new science of change about how pivotal moments in coaching occur and what coaches can do to help ignite substantial change. This book interweaves master coach stories, examples, tools, strategies, and research to inform and enlighten readers of the profound awakening human beings are experiencing to the power of individual choice. No longer constrained by the outdated Newtonian concepts of linear change and external control, individuals are now capable of self-organization by shifting their perceptions and choosing to leave patterns of limited thought and action. From their research, the authors found that coaches play a key facilitative role in helping unleash the capacities and power of these pivots. Readers are invited to reflect on their own experiences of insight and those of their clients and to focus on priming strategies they can use to inspire and support pivotal moments for others. The authors share a dynamic model for igniting substantial change which shows the interrelationship of three core processes that contribute to a person's readiness for a shift: beliefs, inner knowing, and memory--from publisher's website.